A case series of low-level laser therapy treatment in patients with peripheral facial palsy - Basualdo Allende, Javier; Caviedes, Rodrigo; von Marttens, Alfredo; Kuga, Milton [UNESP]; Fernández, Eduardo (Elsevier, 2024)
Background: Peripheral Facial Palsy (PFP) is a facial paralysis with various etiologies, including idiopathic causes (Bell's palsy), infections, trauma, and genetic factors. Traditional treatments involve antiviral medications, corticosteroids, and physiotherapy. However, new therapies, such as Low-Level Laser Therapy (LLLT), are emerging with promising results. Methods: This case series reports on two patients with PFP treated with LLLT combined with Vitamin B1, B6, and B12 supplementation. The first case involved a 52-year-old female with PFP due to a viral infection. The second case was a 33-year-old male who developed PFP following a traumatic brain injury. Both patients received LLLT sessions every two weeks, targeting 10 points along the facial nerve pathway from the facial notch across the face. The laser device used was the Theraphy EC (DMC, Sao Carlos, SP, Brazil), with each point receiving 4 Joules of energy applied perpendicular to the skin after cleaning the face with water and soap to remove lipids that could interfere. The administration of Vitamin B was done using NEUROBIONTA tablets (Vitamin B1 + Vitamin B6 + Vitamin B12; Procter & Gamble, Santiago, Chile) with one tablet taken daily for 30 days. Results: After six to seven sessions, both patients showed significant improvement in facial muscle function and overall facial symmetry. In the first case, improvements were noted in muscle tonicity and facial movements, with the patient reporting reduced facial disfigurement. In the second case, notable recovery in facial mobility and symmetry was observed, with the patient experiencing decreased paresthesia and restored muscle functionality. Conclusion: These findings suggest that LLLT, combined with Vitamin B1, B6, and B12 supplementation, may effectively improve facial muscle function and symmetry in PFP patients. The non-invasive nature and ease of application make LLLT a viable option for PFP treatment. Further studies with larger sample sizes and standardized protocols are necessary to confirm these results and establish LLLT as a standard treatment for PFP.
Keywords: Case series; Facial paralysis; Low-level laser therapy; Peripheral facial palsy; Vitamin B1; Vitamin B12; Vitamin B6